Studies on lantern Fish (Benthosen1a pterotun1) 11 Nuriitional Evaluation - NAIR, A LEKSHMY; JAMES, M ARUL; MATHEW, P T; GOPAKUMAR, K (Fishery Technology, 2017)
Various methods for processing and utilization of lantern fish ( Benthosema pterotum) are reported. Nutritional evaluation of fish meal and fish hydrolysate from lantern fish has been carried out. Growth rate and PER of lantern fish meal are similar and better than that of the reference protein, casein. Lantern fish meal can thereforebe extensively used for the formulation of poultry, fish and other animal feeds as agood protein supplement with beneficial effects.